DIDACTIC POSSIBILITIES OF TRAINING FUTURE TEACHERS OF FINE ARTS IN HIGHER ART PEDAGOGICAL EDUCATION INSTITUTIONS TO FORM COMPETENCES IN ILLUSTRATIVE DRAWING IN SCHOOL STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the systemic didactic opportunities for preparing future fine arts teachers in higher artistic pedagogical educational institutions to develop illustrative drawing competencies in school students. Within the framework of the research, the implementation of the "Double Direction" education model that synthesizes artistic creativity with engineering-technical skills into higher education, the formation of physical and digital environments based on the "Third Teacher" concept in educational design studios, and the utilization of digital portfolio systems for assessing students' creative-pedagogical activities are highlighted. Along with traditional fine arts methods, a methodical system for designing modern illustrative drawing lessons using 3D modeling, computer graphics, and artificial intelligence (AI) technologies is proposed.